1996
DOI: 10.1017/s1074070800007343
|View full text |Cite
|
Sign up to set email alerts
|

Program Participation Behavior of Nonindustrial Forest Landowners: A Probit Analysis

Abstract: This study provides an analysis of nonindustrial private forest (NIPF) landowners' participation in forestry assistance programs. A probit model was used for data collected from a random sample of 329 Indiana landowners. The analysis revealed that total land owned, commercial reasons for ownership, government sources of information, and membership in forestry organizations influenced NIPF landowners' program participation. Age, fear of loss of property rights, and duration since the first wooded tract was acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 12 publications
9
80
1
Order By: Relevance
“…The results of this study indicated that diversification benefits of participating in a PES scheme increased when shifting from the stand level to landscape level. This confirms previous evidence suggesting that voluntary participation in PES contracts increases with land area size (Nagubadi et al 1996;Wilson 1997;Lynch and Lovell 2003;Milder et al 2010). In Figure 8, the landscape level efficiency frontiers are shown, both including and excluding other financial asset classes as alternative investments.…”
Section: Main Contributionsupporting
confidence: 91%
“…The results of this study indicated that diversification benefits of participating in a PES scheme increased when shifting from the stand level to landscape level. This confirms previous evidence suggesting that voluntary participation in PES contracts increases with land area size (Nagubadi et al 1996;Wilson 1997;Lynch and Lovell 2003;Milder et al 2010). In Figure 8, the landscape level efficiency frontiers are shown, both including and excluding other financial asset classes as alternative investments.…”
Section: Main Contributionsupporting
confidence: 91%
“…One additional year of a respondent's age increased the probability of re-enrollment by 3.0% (Table 1). Because farming and reconverting GTGP land plots to agriculture are labor intensive, re-enrolling these land plots in the PES program would be a convenient way for older people to reduce labor demand (34,55). Respondents' gender also affected the program re-enrollment.…”
Section: Effects Of Land Plot Features and Respondents' Characteristicsmentioning
confidence: 99%
“…Several studies about the adoption of new technologies and practices in agriculture revealed that producer's socio-economic attributes play an important role (e.g., Adesina and Chianu, 2002;Banerjee et al, 2008;Kim, Gillespie, and Paudel, 2005;Nagubadi et al, 1996;Nkamleu and Adesina, 2000;Paudel et al, 2008;Rahm and Huffman, 1984;Ward et al, 2008). The age of the primary producer is represented by the variable AGE.…”
Section: The Explanatory Variablesmentioning
confidence: 99%